Incidence of Glaucoma or Ocular Hypertension After Repeated Anti-Vascular Endothelial Growth Factor Injections for Macular Degeneration - Wingard JB (Dove Medical Press, 2019)
Jeremy B Wingard,1 Darcie AP Delzell,2 Nathan V Houlihan,2 Jonathan Lin,2 Jon P Gieser1 1Wheaton Eye Clinic, Wheaton, IL 60187, USA; 2Mathematics and Computer Science Department, Wheaton College, Wheaton, IL, 60187, USACorrespondence: Jeremy B WingardWheaton Eye Clinic, 2015 N. Main Street, Wheaton, IL 60187, USATel +1 630-668-8250Email jbwingard@gmail.comPurpose: To estimate the risk of glaucoma or sustained ocular hypertension (OHT) related to anti-vascular endothelial growth factor (VEGF) injections for age-related macular degeneration (AMD).Design: Retrospective chart review.Subjects: Patients who received unilateral anti-VEGF injections for AMD at the Wheaton Eye Clinic (IL).Methods: Chart analysis was performed on 1095 patients, without prior glaucoma or OHT, who received unilateral anti-VEGF injections for AMD from 2005 to 2012, with data collected through 2013. Data collection included demographics, lens status, date and medication type of each injection, and the date of diagnosis of glaucoma or OHT by a treating glaucoma specialist, which was the main outcome measure. Rare events logistic regression was performed to determine the risk of disease development based on sex, lens status, and injection frequency.Results: Unilateral glaucoma or sustained OHT developed in 42 patients over the course of follow-up, with 40 events in the injected eye only, 2 in the contralateral eye only. Statistical modeling predicted elevated risk for onset of glaucomatous disease with a higher maximum frequency of injections (p < 0.0001, odds ratio [OR] 2.18 for each additional injection over the most injection-intense 6 months for a given subject) and with phakic lens status (p = 0.0009, OR 0.33 for pseudophakia).Conclusion: Our results show a significant risk for glaucoma or OHT development in patients undergoing repeated treatments with intravitreal anti-VEGF injections for AMD, establishing the first reliable connection between disease development and a period of high-frequency injections. In addition, we show a significantly increased risk of disease development in phakic patients, which we believe points to a mechanical explanation for this type of secondary glaucoma.Keywords: exudative macular degeneration, secondary glaucoma, open-angle glaucoma, anti-vascular endothelial growth factor